An index of learning styles among Universiti Teknologi MARA students / Salimah Ahmad, Zakiyah Omar and Nurhidayah Masni Abdullah - Ahmad, Salimah; Omar, Zakiyah; Abdullah, Nurhidayah Masni (2009)
This study aims at finding an index of learning style among students in Universiti Teknologi MARA (UiTM) Pahang so that the lecturers can adapt the teaching style that match the student's preference. An index of learning style questionnaires (ILS) developed by Felder and Solomon was distributed among students from the science and technology, and social sciences faculties in the university. The respondents' feedback was analyzed based on the four domains of learning styles which are active-reflective, sensing-intuitive, visual-verbal and sequential-global. The findings reveal that students, regardless of their nature of studies, were visual, sensory, active and sequential learners. Such findings can become an important tool to better address the student's needs in the learning process.